Fruit Loops & Co / Khairul Ikhwan Mualasan... [et al.] - Mualsan, Khairul Ikhwan; Adzhari, Mohd Hisyam; Sazali, Fathia Anis; Noorham, Nareesa; Awang, Khalilah; Bacho, Nurul Fatin (2015)
This business is based on partnership where it consist of four(4) members which hold important position in the company such as General Manager, Administrative Manager, Marketing Manager, Operational Manager and Financial Manager. The business capital is amounted to RM 90 000.00 where the total contribution of each member RM15 000.00. Sushi Fruits is one of the most popular product in our company. Fruit Loops with the tagline "as sweet as your smile" that are located at lot 38, ground floor One Borneo Hyper mall, Jalan Urns, Kota Kinabalu Sabah. Fruit Loops is company which focus on food production in Malaysia. Sushi is one of the favorite foods in Japan and also in Malaysia. We try hard to innovation the product which is the combination of the sushi rice and fruits. Other products that our company also produce is Casablanca that are using mango as a main ingredients. The texture and color of our product will be the main attraction in our company. Based on our objective, we believe that our business have potential for being profitable business using the all marketing strategies to attract our customers. We expect that our business will become more development in futures with the innovation of fruits. The demand will increase during the accession but in the long term and profitable in future.